Cancer genetics program: Follow‐up on clinical genetics and genomic medicine in Qatar. Issue 6 (16th December 2018) - Al‐Bader, Salha Bujassoum; Alsulaiman, Reem; Bugrein, Hekmet; Ben Omran, Tawfeg; Abbaszadeh, Fatemeh; Bakheet, Nawal; Apsa Kusasi, Sitti; Abdou, Nema; Solomon, Benjamin D.; Ghazouani, Hafedh
Abstract : This article presents an overview of the cancer genetics program in Qatar. In addition to summarizing clinical, research, educational, and other aspects, data related to testing outcomes (over the course of approximately 5.5 years) are presented.